The sisters [large type] : a novel - Jensen, Nancy, 1961- (Thorndike Press large print basic series., 2012)
Growing up in hardscrabble Kentucky in the 1920s, with their mother dead and their stepfather an ever-present threat, Bertie Fischer and her older sister Mabel have no one but each other. But on the day that Bertie receives her eighth-grade diploma, good intentions go terribly wrong. A choice made in desperate haste sets off a chain of misunderstandings that will divide the sisters and reverberate through three generations of women.